Tradisi Poda Na Lima Sebagai Pedagogi Kreatif Dalam Pembelajaran IPS di Era Merdeka Belajar - Siti Maryam; Ritonga, Muhammad Yusuf; Siti Adaniah; Siregar, Lestari (Yayasan Perguruan Kampus, 2024)
Poda Na Lima as a local wisdom value of the Angkola-Mandailing community is considered strategic for developing education in the Tabagsel region (Southern Tapanuli). The Poda Na Lima tradition is considered to be one of the influences on creative education in social studies learning in the Merdeka Belajar era. Social studies subjects aim to produce citizens who are religious, honest, democratic, creative, critical, enjoy reading, have the ability to learn, are curious, care about the social and physical environment, contribute to the development of social and cultural life, and communicate productively. It is hoped that through the strategic role of Poda Na Lima, it can create an educational generation with strong social character, physical and spiritual health in the search and development of knowledge and insight through the educational process. Therefore, Poda Na Lima can be seen as having a strategic role in building quality education in facing the challenges of changing times in the Era Merdeka Belajar.